Gamification in Language Assessment: Challenges and Pedagogical Strategies Across Three Assessment Types in EFL Contexts - Ayuningtryas, Vina; Emaliana, Ive (Journal of Language and Literature Studies, 2025)
Gamification has become a popular learning strategy that incorporates game elements such as points, levels, and badges into learning activities to enhance learners' participation and motivation. It has recently been extended beyond instruction to the field of assessment, where it transforms traditional testing into more interactive and engaging experiences. However, integrating gamification into assessment presents unique challenges that differ from its use in teaching. This narrative review aims to examine the challenges in integrating gamification elements into Assessment for Learning (AfL), Assessment of Learning (AoL), and Assessment as Learning (AaL), and to explore pedagogical strategies for addressing these challenges in EFL contexts. The study analyzed ten peer-reviewed journal articles published from 2014 to 2024 from ScienceDirect and Taylor & Francis, selected based on their relevance to gamification in language assessment. Each study was reviewed to identify recurring challenges and pedagogical strategies for language assessment practices. The results reveal that while gamification can foster learner engagement, challenges remain in aligning game elements with learning objectives, adapting materials to learners’ proficiency levels, and ensuring content validity. Reported pedagogical strategies for improvement include ensuring the contextual relevance of game elements and assessment purposes, aligning gamification with instructional goals, combining traditional and gamified components, providing transparent feedback systems, and integrating teacher guidance in reflective tasks. The study suggests that effective implementation of gamified assessment requires teachers’ strong language assessment literacy and continuous reflection. These insights offer practical implications for EFL educators in designing assessments that are not only engaging but also pedagogically sound and valid.